A Nernstian Biosupercapacitor. Issue 49 (2nd November 2016) - Pankratov, Dmitry; Conzuelo, Felipe; Pinyou, Piyanut; Alsaoub, Sabine; Schuhmann, Wolfgang; Shleev, Sergey
Abstract: We propose the very first "Nernstian biosupercapacitor", a biodevice based on only one redox polymer: poly(vinyl imidazole‐ co ‐allylamine)[Os(bpy)2 Cl], and two biocatalysts. At the bioanode PQQ‐dependent glucose dehydrogenase reduces the Os 3+ moieties at the polymer to Os 2+ shifting the Nernst potential of the Os 3+ /Os 2+ redox couple to negative values. Concomitantly, at the biocathode the reduction of O2 by means of bilirubin oxidase embedded in the same redox polymer leads to the oxidation of Os 2+ to Os 3+ shifting the Nernst potential to higher values. Despite the use of just one redox polymer an open circuit voltage of more than 0.45 V was obtained during charging and the charge is stored in the redox polymer at both the bioanode and the biocathode. By connecting both electrodes via a predefined resistor a high power density is obtained for a short time exceeding the steady state power of a corresponding biofuel cell by a factor of 8. Abstract : Conversion and storage : A Nernstian biodevice utilizing a concentration gradient of immobilized redox species, which are identical on both positive and negative electrodes, generated with the help of redox enzymes, converts chemical energy directly into electrical energy, which is capacitively stored within the same volume used for conversion.